Development of a low-cost mobile mapping system: A South American experience - Da Silva, João Fernando C. [UNESP]; De Oliveira Camargo, Paulo [UNESP]; Gallis, Rodrigo B.A. [UNESP] (Wiley, 2003)
This paper presents the prototype of a low-cost terrestrial mobile mapping system (MMS) composed of a van, two digital video cameras, two GPS receivers, a notebook computer, and a sound frame synchronisation system. The imaging sensors are mounted as a stereo video camera on top of the vehicle together with the GPS antennae. The GPS receivers and the notebook computer are configured to record data referred to the vehicle position at a planned time interval. This position is subsequently transferred to the road images. This set of equipment and methods provide the opportunity to merge distinct techniques to make topographic maps and also to build georeferenced road image databases. Both vector maps and raster image databases, when integrated appropriately, can give spatial researchers and engineers a new technique whose application may realise better planning and analysis related to the road environment. The experimental results proved that the MMS developed at the São Paulo State University is an effective approach to inspecting road pavements, to map road marks and traffic signs, electric power poles, telephone booths, drain pipes, and many other applications important to people's safety and welfare. A small number of wad images have already been captured by the prototype as a consequence of its application in distinct projects. An efficient organisation of those images and the prompt access to them justify the need for building a georeferenced image database. By expanding it, both at the hardware and software levels, it is possible for engineers to analyse the entire road environment on their office computers.
Keywords: Appropriate technology; Bundle block adjustment; Camera calibration; Digital video cameras; Mobile mapping; Road image databases; Street furniture; Database systems; Digital devices; Global positioning system; Imaging systems; Laptop computers; Sensors; Synchronization; Video cameras; Digital video camera; Imaging sensors; Mobile telecommunication systems; digital image; imaging method; mapping method